1996
DOI: 10.1016/0014-5793(96)00302-x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical evidence for the interaction of regulatory subunit of cAMP‐dependent protein kinase with IDA (Inter‐DFG‐APE) region of catalytic subunit

Abstract: To explore the structural basis required for the hoioenzyme formation of cAMP-dependent protein kinase, we have prepared rabbit anti-peptide antibodies that can block the holoenzyme formation without affecting the catalytic activity of the enzyme. The antibodies were raised against a specific site in the catalytic (C)-subunit, termed IDA (Inter-DFG-APE) region, which lies between the kinase subdomains VII and VIII. Although the C-subunit immunoprecipitated with anti-IDA antibodies could not form a stable compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…These residues are distributed about the surface of the C subunit, leaving only a narrow region of the C subunit to which the R subunit might bind that agrees strikingly with the region identified by the fitting of the crystal structures into our two-ellipsoid model of the RC dimer. Also supporting the proposed site of R-C interaction are the data of Sahara et al (39), who have shown that antipeptide antibodies to C subunit residues 187-199 or to residues 187-205 blocked the R-C interaction.…”
Section: -91supporting
confidence: 61%
“…These residues are distributed about the surface of the C subunit, leaving only a narrow region of the C subunit to which the R subunit might bind that agrees strikingly with the region identified by the fitting of the crystal structures into our two-ellipsoid model of the RC dimer. Also supporting the proposed site of R-C interaction are the data of Sahara et al (39), who have shown that antipeptide antibodies to C subunit residues 187-199 or to residues 187-205 blocked the R-C interaction.…”
Section: -91supporting
confidence: 61%
“…Evaluation of Models with Respect to Other Data-The proposed site for the R-C interaction in the R I␣ -based (and R II␤ -based) model is supported by the observation that that anti-peptide antibodies to C subunit fragments 187-199 and 187-205 blocked the R-C interaction (34). The proposed interface site is also compatible with the extensive set of mutation studies of yeast PKA C subunit homolog that identified a group of five residues involved in R subunit interaction and 31 C subunit surface residues unlikely to be at the R-C subunit interface (30, 31) (see "Materials and Methods").…”
Section: Resultsmentioning
confidence: 95%
“…Anti-phosphorylated MAP kinase antibody (#9101S) was from BioLabs (MA, USA). A synthetic tyrosine kinase substrate peptide, Cdc2 peptide (20 amino acids; VEKIGEGTYGVVYKARHKLS), and synthetic IDA (Inter-DFG-APE) peptides; IDA-Src (19 amino acids, LIEDNEYTARQGAKFPIKW), IDA-PKA (20 amino acids with a nonauthentic cysteine in the C-terminus, FAKRVKGRTWTLCGTPEYLC), IDA-MAPK (25 amino acids with a nonauthentic cysteine in the C-terminus, LARVA-DPDHDHTGFLTEYVATRWYRC), and IDA-EGFR (20 amino acids, LLGAEEKEYHAEGGKVPIKW) were synthesized and puri®ed as described (Fukami et al 1993;Sato et al 1995b;Sahara et al 1996;Tokmakov et al 1996). The tyrosinephosphorylated form of IDA-Src peptide (P-IDA-Src) was purchased from Sawadii Technology (Tokyo).…”
Section: Chemicals Antibodies and Peptidesmentioning
confidence: 99%